The Inventors Role: Was Schumpeter Right? - Pontus Braunerhjelm; Roger Svensson (Research Institute of Industrial Economics (IFN), 2007)
According to Schumpeter, the creative process of economic development can be divided into three distinguishable stages of invention, innovation (commercialization) and imitation. We show why there is a rationale for the Schumpeterian entrepreneur to also include the inventor in the innovation process. In addition, we provide a framework where the theories of Knights risk defining entrepreneur and Schumpeters innovative entrepreneur can be bridged. Merging the two enhances the possibilities of successful commercialization since the inventor may further adapt the innovation to customer needs, transmit information and reduce uncertainty. This serves to expand the market opportunities for the entrepreneur. The empirical analysis is based on a survey covering Swedish patents granted to individuals and small firms, with a response rate of 80 %. The results show improved commercialization performance when the patent is licensed or sold to an entrepreneur, or if the inventor is employed in an entrepreneurial firm, as compared to commercialization in the inventors own firm. Another important result is that, irrespective of commercialization mode, an active involvement of the inventor is shown to have a positive impact on performance.
Keywords: M13; O31; O32; 330; Entrepreneur; Inventor; Innovations; Commercialization; Entrepreneurship-Ansatz; Industrielle Forschung; Innovation; Innovationsmanagement; Schumpeterismus; Schweden